Odpowiedzi

2010-03-11T18:22:14+01:00
A)x=1-3(x+1)
x= 1 - 3x -3x
x + 3x+3x=1
7x=1/:7
x=..
itd..
2010-03-11T18:35:55+01:00
A. x= 1-3(x+1)
x= 1-3x-3
x+3x=-2
4x=-2
x=-1/2
b.(x+1)-(x-1)=1
x+1-x+1=1
0=-1
c. 1/2(x-1)=4
1/2x-1/2=4
1/2x=9/2
x=9
d.1/4(2)(x*1/2)-3(x+1/3)=0
1/4*2*1/2x-3x-1=0
11/4x=1
x=4/11
e.(x+2)6=0,5x
6x+12=0,5x
5,5x=-12
x=24/11
f.0,1(x+2)=0,2x
0,1x+0,2=0,2x
0,2=0,1x
x=0,5
g.6(1-1/3x)=2(1+1/2x)
6-2x=2+x
6-2=2x+x
4=3x
x=4/3
h. 0,3x-2(0,1x+1)=0
0,3x-0,2x-2=0
0,1x=2
x=20
i.0,5(x-3)+0,25(2x+6)=5
0,5x-1,5+0,5x+1,5=5
x=5